A enfermagem brasileira frente ao envelhecimento populacional: cenários possíveis para 2025 - Clarissa Terenzi Seixas Cougo (2007)
The aging process of the population constitutes an important world-wide movement. In Brazil, this movement happened more recently and faster, in middle of deep social, economic, cultural inequalities when compared to developed countries. These modifications bring new demands and necessities, requiring policies to act in this scenario. Nursing, because of its importance as a social practice and for its undeniable role in the aged people care, possess conditions to answer properly to these challenges. Thus, to understand what has been done by the Brazilian nursing constitutes a basic element for the preparation and the planning of actions, turning these professionals able to impact the future of the health system and the society. This study has, as general objective, to analyze the performance of Brazilian nursing and its contribution to the Brazilian aging process. It intends, also, to analyze the challenges that the aging process of the population brings to Brazilian society and to construct scenarios for the Brazilian nursing in 2025 front to the challenges of the aging process. Qualitative study guided by the dialectic and carried through in observance to the ethical norms of the Resolution 196/96 of the Brazilian National Advice of Health. The persons interviewed in this study were a representative or policy-maker in the nursing matters of the following entities: Federal Advice of Nursing; Brazilian Association of Nursing; National Advice of Scientific and Technological Development; Coordination of Perfectioning of Staff of Superior Level; Ministry of Education and Culture; Health Department. The technique of individual interview with half-structuralized script was used as an instrument to collect data of primary source and, for the data of secondary source, the methodological resources of the systematic bibliographical research were used. The method of analysis of content proposed by Bardin (1979) was used. For the construction of the future scenarios, the methodologies used were those proposed by Rogers (1997) and Villeneuve & MacDonald (2006), that consider the elaboration of possible scenarios, desirable or not. Through the analysis of the current scenario it was possible to understand the ways nursing have to impact the future of the profession, of the health system and of the society. The analysis evidenced that nursing, historically, presents a trend to political passivity, not questioning the ethical values and the ideology expressed in the policies that concern its practice and health. Although the aging process generates challenges that affect nurses directly, they little have influenced the policies and laws in the area. Nursing already recognized this exclusion of the decisional processes as a barrier for the advance of the profession and for the quality of the attention practiced, however, havent get organized in an effort to influence policy-making. To increase the capacity to act in the agenda definition, the professionals need for mobilization was evident, reestablishing the associative entities as spaces for collective battle. The importance of making changes in nursing education was also patent in the analysis, therefore it still presents a little flexible character to changes observed in health. The inclusion of new practices and theories that allow nurses to act in the properly in questions related to the aging population has been insufficient and reflects in its capacity to contribute for a desirable future for the aged ones. It was proven necessity of nursing to reassume the care as object of its work and to occupy its role to manage care, materializing it in its assistential social and political practice. In this context, the attention to the aged person and its family constitutes a strategy for the reorganization of nursing work, demanding the reformularization of the practice and resignifying care as object of its work. It was possible to conclude that the creation of future scenarios constitutes interesting strategy to identify challenges and to plan action in order to contribute for the accomplishment of a desired future, through well informed choices. It is essential for nursing to analyze the possibilities and to decide for acting to influence the construction of a favorable scenario for the profession, for the health of the population in general and for the aged people in particular and to take measures for making them real. This attitude (or the lack of it) will make all the difference in 2025.